Families divided: disruption of the family in zimbabwe’s fast track land reform programme - Nyawo, Vongai Z. (Unkown, 2016)
Events in the last decade around the land question in Zimbabwe and the broader political contexts in which they have played out have been dramatic and transformative around the family fabric. The political history and the political economy continue to mould the quality of life for most families in significant ways. The family is a pillar of society as it influences the way society is structured, organized and functions, yet the Fast Track Land Reform Programme of 2000 in Zimbabwe came with disruptive tendencies to the family fabric and disadvantaged especially women. This paper targets the notion of split households as families spread their risk through maintaining dual farming households as fall back plan if ever they were evicted in one farm. The research sets out to establish the nature and extent of split households resulting in increased insecurity for the family unit, some women and their children. The study also examins how new farmers have invested in new marital and cohabitation relationships in order to manage split households as well as how the structure of the family as it stood in the fast track exposed women to challenges of all kinds. Desktop research and also interviews were carried out with members of families that split as well as with citizens who witnessed the Fast Track Land Reform Programme (FTLRP). Recommendations are that the government should carry out a programme that campaigns for the promotion of family values, for families that were split by the land reform to get back together or restore the traditional respectability of the family.